Report of an ad hoc meeting of the Chairs, Vice-Chairs and Central Crop Database Managers of the Solanaceae and Cucurbits Working Groups, 11-12 April 2013, Valencia, Spain - Bioversity International (2013)
Report of an ad hoc meeting of the Chairs, Vice-Chairs and Central Crop Database Managers of the Solanaceae and Cucurbits Working Groups, 11-12 April 2013, Valencia, Spain